Polynomials in Fp[x] Which Commute Under Composition - Hatley, Jeffrey; Teplitskiy, Mayah (The PUMP Journal of Undergraduate Research, 2023)
Let F be a finite field and let f be a linear polynomial in F[x]. We investigate the number of polynomials of degree d which commute with f under composition. In so doing, we rediscover a result of Park, but with a conceptually simpler proof.